Respuesta :
The difference of the given fraction is expressed as [tex]\frac{x^2+4x-1}{x(x+2)}[/tex]
Given the expression:
- [tex]\frac{x+5}{x+2}-\frac{x+1}{x^2+2x} \\[/tex]
Take the LCM of the fraction to have:
[tex]=\frac{x+5}{x+2}-\frac{x+1}{x(x+2)} \\=\frac{x(x+5)-(x+1)}{x(x+2)} \\=\frac{x^2+5x-x-1}{x(x+2)}\\=\frac{x^2+4x-1}{x(x+2)}[/tex]
Hence the difference of the given fraction is expressed as [tex]\frac{x^2+4x-1}{x(x+2)}[/tex]
Learn more on fractions here; https://brainly.com/question/78672